Nursing home research in Jinan, China: a focus group approach - Wu, Min; Li, Shi Xue; Zhang, Ning Jackie; Zhu, Ai Ai; Ning, Bo; Wan, Thomas T H; Unruh, Lynn (International journal of public policy, 2012)
This qualitative research using the focus group approach has gathered pertinent perceptions from the stakeholders in Chinese elderly care environment, including community-based and institutionalised elderly, medical providers, administrators and governmental officials. The study found that the elderly are willing to live in nursing homes when they are not in good physical condition and are dependent on others for their activities of daily living. The utilisation of nursing home care has gained acceptance in the community as more elders recognise its advantages. The elderly study subjects expressed interest in the service environment, as well as the cultural and recreational activities in nursing homes. Most participants were satisfied with the quality of nursing care. Administrators and providers in the nursing homes agreed that skilled nursing facilities appear to be more competitive because they require more licensed providers and other professional staff members. A majority of nursing homes face serious financial difficulties.